Tumor Cell-Derived Exosomal Circ-0072088 Suppresses Migration and Invasion of Hepatic Carcinoma Cells Through Regulating MMP-16 - Lin, Ye; Zheng, Ze-Hao; Wang, Jian-Xi; Zhao, Zhen; Peng, Tian-Yi (Frontiers in Cell and Developmental Biology, 2021)
Background: Tumor-derived exosomes (EXOs), commonly differentially expressed in circular RNAs, have been shown to be crucial determinants of tumor progression and may regulate the development and metastasis of hepatic carcinoma (HCC). Methods: Possibly differentially expressed circRNAs in patients with HCC were screened out from the Gene Expression Omnibus (GEO). EXOs were isolated from the culture medium of HCC cells and plasma of patients with HCC, followed by characterization by transmission electron microscope, NanHCCight, and western blotting. Additionally, RNA immunoprecipitation and luciferase reporter gene assays were carried out to explore the molecular mechanism of hsa_circRNA_103809 (circ-0072088) in HCC cells. Results: The screening results showed that circ-0072088 was highly expressed in patients with HCC, and its increase indicated unfavorable prognosis of patients according to quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Additionally, circ-0072088 was mainly secreted by HCC cells via EXOs in plasma of such patients, and its high level in plasma EXOs was closely associated with tumor node metastasis (TNM) staging and tumor size. Moreover, HCC-secreted EXOs mediated the degradation of miR-375 via circ-0072088 and upregulated MMP-16, thus suppressing the metastasis of HCC. Conclusion: Upregulated in patients with HCC, circ-0072088 may be an index for diagnosis and prognosis of HCC. In addition, HCC-derived EXOs coated with circ-0072088 might be a treatment for HCC, with the ability to inhibit the metastasis of HCC cells.